Diagnostic and Prognostic Values of PTEN Expression in Functional and Pathological Endometrial Biopsies - Allithy, Amal Nooredeen; Ammar, Islam Mohamed Magdi; Mohammed, Maisa Hashem (Asian Pacific Journal of Cancer Biology, 2022)
Background: Endometrial carcinoma is the most common gynecological malignancy in developed countries. About 80% of endometrial carcinomas are preceded by atypical endometrial hyperplasia. PTEN is a tumor suppressor gene involved in many vital intracellular biological processes. PTEN is altered in more than 45% of endometrial carcinomas. The aim of this study was to evaluate the value immunohistochemical expression of PTEN in normal, hyperplastic and neoplastic endometrial tissues. Methods: Ninety-two endometrial samples were enrolled in this study. They were classified into normal (n=6), hyperplastic (n=54) and neoplastic (n=32) endometrial tissues. Formalin-fixed and paraffin-embedded tissue blocks were prepared from each specimen. Tissue sections were immunohistochemically stained by anti-PTEN antibodies. Results: In our study; PTEN was strongly expressed in all normal and hyperplastic endometrial tissues without atypia. Staining intensity was decreased in atypical endometrial hyperplasia and endometrial carcinoma (p<0.0001). we also detected an inverse relationship between PTEN expression on one side and tumor grade (p=0.006), stage (p< 0.0001) and myometrial invasion (p=0.001) on the other side. Conclusions: Our study proved that immunohistochemical expression of PTEN is down-regulated in atypical hyperplastic and neoplastic endometrial tissues. Evaluation of PTEN expression can be useful as a screening method to detect the potentially precancerous hyperplastic lesions.